2009
DOI: 10.3802/jgo.2009.20.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and prognostic factors in uterine cervical cancer patients treated with postoperative extended field radiation therapy

Abstract: Objective: To evaluate treatment outcomes and prognostic factors in uterine cervical cancer patients treated with postoperative extended field radiation therapy (POEFRT) with or without chemotherapy. Methods: Between 1983 and 2006, 35 patients with a pathologically confirmed positive para-aortic node (PAN) or common iliac node (CIN) who underwent a radical hysterectomy with bilateral pelvic lymph node dissection and PAN dissection received POEFRT with (N=23) or without (N=12) chemotherapy. Prognostic factors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…10,16 In the present study, we found the OS rate to be 71.5%, which compares favorably with those reported in previous studies. 10,16 Extended-field IMRT concomitant with chemotherapy was effective in preventing in-field failure. The locoregional in-field control rate was good, with distant sites being the most common sites of failure.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…10,16 In the present study, we found the OS rate to be 71.5%, which compares favorably with those reported in previous studies. 10,16 Extended-field IMRT concomitant with chemotherapy was effective in preventing in-field failure. The locoregional in-field control rate was good, with distant sites being the most common sites of failure.…”
Section: Discussionsupporting
confidence: 91%
“…Because Kim et al 10 reported that the addition of concurrent chemotherapy to postoperative EFRTwas superior to the use of radiation alone in patients with a pathologically confirmed PAN or CIN metastasis, postoperative EFRT combined with chemotherapy was considered in patients with a pathologically confirmed PAN or CIN metastasis in our institution. Very few studies have suggested the remedial model of postoperative EFRT with concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result brought up the idea that initial molecular evaluation of primary tumor tissue could be helpful in selecting appropriate and individualized drugs for better tumor response to CCRT and with fewer complications possibly in advanced cervical cancer. An article by Kim et al 5 in this issue reports that concurrent extended field radiation and chemotherapy improved 5 year survival rate of 61% in patients with metastatic para-aortic nodes in early stage cervical cancer compared to postoperative radiation only. A recent report with concurrent paclitaxel and cisplatin during extended field radiation in patients with pos-itive paraaortic nodes and locally advanced stage cervical cancer showed promising results with improved survival rate of 56% at the time of report.…”
mentioning
confidence: 99%
“…In this issue of Journal of Gynecology Oncology, there are 3 articles dealing with cervical cancer either with locally advanced tumor or with metastatic nodes at paraaortic region found at the time of operation. [3][4][5] Radiation has been the primary treatment modality for locally advanced cervical cancer (FIGO stage IB2-IVA). Weekly cisplatin is a standard one as a concurrent chemo-radiotherapy with improved local control and survival.…”
mentioning
confidence: 99%